MalaSelect: A Selective Culture Medium for Malassezia Species - Abdourahim Abdillah; Stéphane Ranque (Journal of Fungi, 2021)
Malassezia species are fastidious and slow-growing yeasts in which isolation from polymicrobial samples is hampered by fast-growing microorganisms. Malassezia selective culture media are needed. Although cycloheximide is often used, some fungi, including the chief human commensal Candida albicans, are resistant to this compound. This study aimed to test whether the macrolide rapamycin could be used in combination with cycloheximide to develop a Malassezia-selective culture medium. Rapamycin susceptibility testing was performed via microdilution assays in modified Dixon against two M. furfur and five Candida spp. The MIC was the lowest concentration that reduced growth by a minimum of 90%. Rapamycin ± cycloheximide 500 mg/L was also added to FastFung solid, and yeast suspensions were inoculated and incubated for 72 h. Rapamycin MICs for Candida spp. ranged from 0.5 to 2 mg/L, except for C. krusei, for which the MIC was >32 mg/L. M. furfur stains were rapamycin-resistant. Rapamycin and cycloheximide supplementation of the FastFung medium effectively inhibited the growth of non-Malassezia yeast, including cycloheximide-resistant C. albicans and C. tropicalis. Based on our findings, this “MalaSelect” medium should be further evaluated on polymicrobial samples for Malassezia isolation and culture.